Staggered boards and long-term firm value, revisited - Cremers, K.J. Martijn; Litov, Lubomir P.; Sepe, Simone M. (Journal of Financial Economics, 2017)
This paper revisits the association between firm value (as proxied by Tobin’s Q) and whether the firm has a staggered board. As is well known, in the cross-section firms with a staggered board tend to have a lower value. Using a comprehensive sample for 1978 – 2011, we show an opposite result in the time series: firms that adopt a staggered board increase in firm value, while de-staggering is associated with a decrease in firm value. We further show that the decision to adopt a staggered board seems endogenous, and related to an ex ante lower firm value, which helps reconciling the existing cross-sectional results to our novel time series results. To explain our new results, we explore potential incentive problems in the shareholder-manager relationship. Short-term oriented shareholders may generate myopic incentives for the firm to underinvest in risky long-term projects. In this case, a staggered board may helpfully insulate the board from opportunistic shareholder pressure. Consistent with this, we find that the adoption of a staggered board has a stronger positive association with firm value for firms where such incentive problems are likely more severe: firms with more R&D, more intangible assets, more innovative and larger and thus likely more complex firms.